THE EFFECT OF GLYCEROL CONCENTRATION IN TRIS GLUCOSE EGG YOLK EXTENDER ON THE QUALITY OF TIMOR DEER FROZEN SEMEN - Nalley, W.M.M.; Handarini, R.; Yusuf, T.L.; Purwantara, B.; Semiadi, G. (Diponegoro University, 2011)
The aims of study was to compare the glycerol concentration in Tris glucose egg yolk (TGEY)diluents on the quality of deer frozen semen. Semen was collected from 5 Timor deer usingelectroejaculator. Immediately after collection the semen was evaluated macroscopic andmicroscopically. After initial evaluation, the semen was divided into three tubes and extended with Trisegg yolk with three different glycerol concentrations, which were 10% (TGEY10); 12% (TGEY12) and14% (TGEY14). The sperm motility, viability, acrosome intact and membrane intact were evaluated inraw semen, after equilibration and after thawing. The results showed that there were no differences(p>0.05) on the sperm motility, viability as well as sperm acrosome intact. Sperm membrane intact inTGEY10 (52.50±5.89%) and TGEY14 (51.50±4.12 %) were higher (p<0.05) than in TGEY12(49.00±6.58). It was concluded that 10, 12 or 14% glycerol concentration can be used for Timor deersemen cryopreservation.